A waste valorization strategy for the synthesis of phenols from (hetero)arylboronic acids using pomegranate peel ash extract. Issue 2 (3rd April 2022) - Lakshmidevi, Jangam; Ramesh Naidu, Bandameeda; Avula, Satya Kumar; Majhi, Anjoy; Chia, Poh Wai; Al-Harrasi, Ahmed; Venkateswarlu, Katta
ABSTRACT: Phenols are prominent in organic reactions and highly significant biologically active substances. We report a versatile and sustainable CuI-catalyzed protocol for their synthesis through an oxidative ipso -functionalization (hydroxy deborylation) strategy of (hetero)arylboronic acids [(H)ABAs] using the water extract of pomegranate peel ash (WEPA) in open-air. They are formed at room temperature (RT). This process shows high significance toward the environmental sustainability over the reported procedures of ipso -hydroxylation of (H)ABAs. The application of a waste-derived biorenewable basic reaction medium, air as an oxidant, wide substrate scope, high functional group tolerance, reusability of the catalyst, ambient conditions, less expensive and safer catalyst with low loading, aqueous medium, avoidance of volatile organic solvents, and external oxidant, and tremendous further scope are the noteworthy features of this protocol. GRAPHICAL ABSTRACT: UF0001